2007
DOI: 10.1016/j.expneurol.2006.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Novel two-dimensional morphometric maps and quantitative analysis reveal marked growth and structural recovery of the rat hippocampal regions from early hypothyroid retardation

Abstract: Effects of postnatal hypothyroidism and recovery from this condition on regional growth of the rat hippocampus (HC) were studied using two-dimensional (2D) foldout, morphometric maps of HC and its constituent CA1-CA4 regions. The maps were derived from unfolding serial coronal sections of the rat forebrain, consisting of the entire rostrocaudal extent of HC pyramidal cell layer in the normal control and hypothyroid weanling (P25, postnatal day 25) and young adult (P90) male rats, as well as animals allowed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 78 publications
3
9
2
Order By: Relevance
“…In addition to reductions in body weight, the hypothyroid pups showed all the classical signs of developmental hypothyroidism such as delayed eye and ear opening, infantile fur and reduced movements and playing activity. These results were very similar to our previously published reports (Farahvar and Meisami, 2007; Paternostro and Meisami, 1993). Interestingly, while the body weights of the hyperthyroid pups were generally unaffected by the treatment, they all showed all the classic signs of developmental hyperthyroidism in the rat, such as accelerated body development and maturation, earlier eye and ear opening, and earlier development of fur and facies, and an apparent reduction in body fat, as reported in our previous publications (see Paternostro and Meisami, 1991).…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…In addition to reductions in body weight, the hypothyroid pups showed all the classical signs of developmental hypothyroidism such as delayed eye and ear opening, infantile fur and reduced movements and playing activity. These results were very similar to our previously published reports (Farahvar and Meisami, 2007; Paternostro and Meisami, 1993). Interestingly, while the body weights of the hyperthyroid pups were generally unaffected by the treatment, they all showed all the classic signs of developmental hyperthyroidism in the rat, such as accelerated body development and maturation, earlier eye and ear opening, and earlier development of fur and facies, and an apparent reduction in body fat, as reported in our previous publications (see Paternostro and Meisami, 1991).…”
Section: Resultssupporting
confidence: 93%
“…Following our previously published procedures (Farahvar and Meisami, 2007; Paternostro and Meisami, 1993; Tamasy et al, 1986a,b), developmental hypothyroidism was induced by adding the antithyroid goitrogen, propylthiouracil (PTU, 6‐n‐propyl‐2‐thiouracil; Sigma, St. Louis) to the drinking water of the litter at a concentration of 0.1% (w/v), from birth till the days of sacrifice (P1, P5, P10 and P21). On the recommendation of the University of Illinois veterinarian and following the practice described in our previous publications (Farahvar and Meisami, 2007; Paternostro and Meisami, 1993; Tamasy et al, 1986a,b), a small amount of a non‐caloric sweetener (saccharin) was added to the water bottles of the hypothyroid litters, at the concentration of 0.01 mg/L, to mask the bitter taste of PTU and prevent reduced water intake. Our previous studies have shown that PTU administration plus the artificial sweetener results in adequate water intake, decreased plasma T 4 levels by 100% and a several‐fold increase in plasma TSH levels (Farahvar and Meisami, 2007; Paternostro and Meisami, 1991, 1993; Tamasy et al, 1986a,b).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations